(untitled) (Public Sector Economics - submission site, 2023)
The practice of fostering citizen participation in public finance-related decision making at local government level in North Macedonia and Slovakia has backslid during COVID-19. Since COVID-19 prompted a worldwide lockdown, governments were forced to introduce emergencies and/or develop “new” participation methods. The paper aims to explore the impact of COVID-19 on citizens’ participation in financial decision-making using participatory budgeting among the local self-governments in North Macedonia and Slovakia and identify possible COVID-19-specific and general barriers to such participation, considering the particular context of the two countries.